2019
DOI: 10.1590/0034-7167-2018-0579
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of software with the nursing process for innovation units

Abstract: Objective: To adapt data collection of the Information System software with the nursing process in Intensive Therapy for use in medical and surgical clinic units. Methods: A descriptive study developed in three stages. The first consisted of team training; in the second, the software was applied in clinical practice with 100 patients; and in the third, we analyzed the modifications to be done. Results: There was inter-observer agreement of 91%, followed by application of the software in 100 patients. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
6
0
7
Order By: Relevance
“…Based on the literature review, no negative attitudes about comprehensive nursing process software (including all nursing process stages) were found in the studies. Furthermore, in most studies using non-comprehensive software heath care providers reported lower positive attitudes of the efficiency of the software [38][39][40][41]. However in some studies, negative attitudes of the participants about nursing information technology programs were identified [28,35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature review, no negative attitudes about comprehensive nursing process software (including all nursing process stages) were found in the studies. Furthermore, in most studies using non-comprehensive software heath care providers reported lower positive attitudes of the efficiency of the software [38][39][40][41]. However in some studies, negative attitudes of the participants about nursing information technology programs were identified [28,35].…”
Section: Discussionmentioning
confidence: 99%
“…Para Jarvis (17) , trata-se de um momento essencial para realização do exame, pois é nesse momento que o profissional (14,17) . Outros estudos evidenciam a importância desse momento, uma vez que o preparo inicial pré-exame físico corrobora para a execução da entrevista de enfermagem e o exame físico, onde ambos constituem a primeira etapa do processo de enfermagem, essencial para a operacionalização das atividades do enfermeiro (18,19) .…”
Section: Sessão 1 -Preparo Inicialunclassified
“…Among them, mobile device applications stand out for overcoming the limitations of mobility, since smartphones are a pocket computer that can accompany users 24 hours a day. This quality is essential for resources used in health care (8)(9)(10)(11)(12) , including those that support development of the NP.…”
Section: Introductionmentioning
confidence: 99%